Music Therapy and Bibliotherapy to Reduce Child Anxiety When Given Intravenous Therapy - Heryyanoor Heryyanoor; Muhsinin Muhsinin; Rahmawati Rahmawati; Fitriyanti Patarru'; Febrina Secsaria Handini; Basilius Yosepfus Weu (Universitas Airlangga, 2019)
Introduction: Children often experience anxiety when undergoing the treatment process at the hospital. Efforts to reduce such anxiety can be done with music therapy and bibliotherapy. This study aims to analyze the differences in the effectiveness of music therapy and bibliotherapy in reducing anxiety in children before getting intravenous therapy.Methods: The research design was quasi-experimental, with the pretest and posttest approach. The population was 178 with 32 samples, each of the 16 respondents were given music therapy and bibliotherapy using a purposive sampling technique. Data were collected with observation sheets from the adoption of the HAM-A scale, analyzed by the Wilcoxon test and independent T test at a significance level of p ≤ 0.05.Results: There were differences in children's anxiety when getting intravenous therapy before and after music therapy and bibliotherapy with p = 0.001 (p <0.05), and there was no difference in the effectiveness of the two p values = 0.91 (p> 0.05), but the average bibliotherapy reduced anxiety by 65%, and music therapy by 57%.Conclusion: Bibliotherapy can be given as complementary therapy in children before intravenous therapy.